Assessing Newly Isolated Entomopathogenic Fungi for Amylase and Cellulase Enzymes Production - Chin, Nee Nee (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Negative implications resulted from extensive use of chemical pesticides have triggered study of microorganisms in pest control. With this, entomopathogenic fungi (EPF) which are natural enemies of insects are discovered to be biopesticides due to their pathogenicity that is associated with their degrading enzymes. However, as degrading enzymes there is little evidence showing that amylase and cellulase can be produced by EPF. Thus, this study is aimed to determine amylase and cellulase activity through screening, DNS and spectroscopic methods in order to evaluate potential of newly isolated EPF as a source of these enzymes. EPF were screened for amylase and cellulase production on starch and CMC agar based on halo formation. Out of three EPF screened, all of them showed positive activity reaction with starch whereas only one EPF showed cellulase activity. EPF with the highest enzyme activity were used in the fermentation. The highest amylase and cellulase activity were recorded at 0.5462 IU/mL and 0.0816 IU/mL respectively. Strain UK1 can produce both amylase and cellulase but strain 19.1 mid yields higher amylase production. Hence, strain 19.1 mid is a good source for amylase production while strain UK1 is a source for amylase and cellulase production.